Analysis of understanding business strategy in contemporary management perspective: Literature study - Nikhlatul Khasanah; Rosa Amanda Putri (Indonesia Accounting Research Journal, 2025)
This literature review synthesizes contemporary perspectives on business strategy in the rapidly evolving landscape of digital innovation and sustainability. Central to the discussion are dynamic capabilities and strategic agility as essential mechanisms enabling organizations to adapt and thrive amid volatile and complex environments. The integration of digital technologies and artificial intelligence is explored as a transformative force reshaping traditional strategic frameworks, necessitating new leadership approaches and organizational cultures that foster innovation. The role of sustainability is highlighted, emphasizing its growing influence on firm performance and stakeholder value creation. Moreover, the review addresses the transient nature of competitive advantage in the current business context, underscoring the importance of continuous adaptation and strategic renewal. Collectively, these studies offer a comprehensive understanding of how firms can leverage strategic management principles to achieve sustainable growth and competitive differentiation in the digital era.